2001
DOI: 10.1007/pl00001352
|View full text |Cite
|
Sign up to set email alerts
|

Effects of stream acidification and habitat on fish populations of a North American river

Abstract: Water quality, physical habitat, and fisheries at sixteen reaches in the Neversink River Basin were studied during 1991 -95 to identify the effects of acidic precipitation on stream-water chemistry and on selected fish-species populations, and to test the hypothesis that the degree of stream acidification affected the spatial distribution of each fish-species population. Most sites on the East Branch Neversink were strongly to severely acidified, whereas most sites on the West Branch were minimally to moderate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 38 publications
2
25
0
Order By: Relevance
“…For instance, many streams increase in pH as water moves downstream and the area of the contributing watershed increases (Schofield and Driscoll 1987). Even in headwater streams, some sections may be influenced by seepage from well-buffered groundwater and may represent a refuge for fish in an otherwise acidified stream (Baldigo and Lawrence 2001). Similarly, some invertebrates in a lake may escape from acidified water by sheltering in the well-buffered sediments on the bottom of the lake.…”
Section: Aquatic Ecosystemsmentioning
confidence: 99%
“…For instance, many streams increase in pH as water moves downstream and the area of the contributing watershed increases (Schofield and Driscoll 1987). Even in headwater streams, some sections may be influenced by seepage from well-buffered groundwater and may represent a refuge for fish in an otherwise acidified stream (Baldigo and Lawrence 2001). Similarly, some invertebrates in a lake may escape from acidified water by sheltering in the well-buffered sediments on the bottom of the lake.…”
Section: Aquatic Ecosystemsmentioning
confidence: 99%
“…Biomass of Fish Populations-Biomass may be a better gage (of the effects of releases on fish communities) than density because biomass tends to fluctuate less widely than density (it is more conservative) when fish react to biotic, habitat, and water-quality stresses (Baldigo and Lawrence, 2001). Biomass data for species populations in this study were, in fact, much less variable among sites (total biomass varied 16-fold) than density (total density varied 103-fold) (tables 18, 19).…”
Section: Fish Communitiesmentioning
confidence: 99%
“…Similarly, under natural conditions, bioassay studies have demonstrated that low pH and high aluminum levels are the factors most closely associated with fish mortality during episodic acidification events (Simonin et al 1993;Van Sickle et al 1996;Baldigo and Murdoch 1997). Baldigo and Lawrence (2001) evaluated a large suite of stream characteristics and found that pH and aluminum concentrations during episodic acidification in streams of the Catskill Mountains explained a substantial proportion of the variability in fish abundance. In that study, habitat alone was rarely as important as chemistry alone, and the greatest proportion of the variation in Brook Trout abundance was accounted for when both chemical and physical factors were evaluated together (Baldigo and Lawrence 2001).…”
Section: Introductionmentioning
confidence: 98%
“…Alternatively, in well buffered streams, physical habitat features such as pools are more closely associated with fish biomass (Stichert et al 2001). In environments that are affected by both acid deposition and habitat modifications such as the streams in eastern North America and northern Europe, measurements of acidification in conjunction with measurements of habitat may be the most effective overall method to account for variability in the biomass of fish in headwater systems (Baldigo and Lawrence 2001). In this study we develop a simple empirical model to estimate fish biomass in headwater streams in the northeastern US from a few easily measured metrics that reflect both stream habitat and stream buffering capacity.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation